Geni TBX e patologia umana - Romagno, Daniela (Scuole di dottorato, 2002)
TBX genes belong to a family of homeotic genes (t-boxes) for which it has been proved that gene mutations have serious consequences on the development. In particular, there is significant evidence to support the involvement of the TBX1 gene in DiGeorge / Velocardiofacial syndrome (DGS/VCFS) and it has been proved that the TBX3 and TBX5 genes are implicated, respectively, in UMS (Ulnar Mammary Syndhrome) and in Holt-Oram syndrome (HOS). The book collects information available in the literature up to October 2001 on human TBX genes. The review of the data allowed to come to interesting considerations and offers ideas for orienting further research.